Reach out : the simple strategy you need to expand your network and increase your influence - Beck, Molly (McGraw-Hill Education, 2018)
Whether youre just starting out; changing jobs; or well-established and just eager to know more people; this practical guide will help you turn career dreams into professional success by helping you connect with others who can put you on the fast track. --